2015
DOI: 10.5114/jcb.2015.55118
|View full text |Cite
|
Sign up to set email alerts
|

MITHRA – multiparametric MR/CT image adapted brachytherapy (MR/CT-IABT) in anal canal cancer: a feasibility study

Abstract: PurposeThe aim of this study is to test a novel multiparametric imaging guided procedure for high-dose-rate brachytherapy in anal canal cancer, in order to evaluate the feasibility and safety.Material and methodsFor this analysis, we considered all consecutive patients who underwent magnetic resonance/computed tomography image adapted brachytherapy (MR/CT-IABT) treated from February 2012 to July 2014. To conduct this project, we formed a working group that established the procedure and identified the indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The knowledge of a proctologist/gynecologist is necessary for optimal orientation and performance of the implantation technique, as well as the presence of an anesthetist at the implantation procedure is obligatory. [22][23][24] In breast cancer IRT, independently from the fact of a planned partial breast or boost implantation, multidisciplinary decision-making is obligatory. The cooperation of imaging experts, pathologists, breast surgeons and IRT/EBRT experts offers the best possible treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of a proctologist/gynecologist is necessary for optimal orientation and performance of the implantation technique, as well as the presence of an anesthetist at the implantation procedure is obligatory. [22][23][24] In breast cancer IRT, independently from the fact of a planned partial breast or boost implantation, multidisciplinary decision-making is obligatory. The cooperation of imaging experts, pathologists, breast surgeons and IRT/EBRT experts offers the best possible treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting the long-term outcome of IMRT reported either no or very rare incidence of Grade 3 or higher late sequelae [14,58,61,97,98,[129][130][131]. Three studies found only the gross tumor volume (GTV) dose to be predictive of acute Grade 2 GI toxicity [132][133][134].…”
Section: Radiotherapy Technique and Dosage And Their Influence On Latmentioning
confidence: 99%
“…In particular, there is evidence, which has proven that in selected cancers, such as cervical and prostate cancer, BT boost vs. no boost increases overall survival after external beam radiation therapy [8,9,10]. Moreover, there is evidence that the use of intensity modulated or stereotactic radiation therapy as alternatives to BT boost resulted in worse results not only in terms of overall survival, but also with regards to aesthetic results, and function and organ preservation [11,12,13,14].…”
Section: Airo Interventional Radiotherapy Study Group "State Of the Amentioning
confidence: 99%